Factors that influence purchase intention social commerce TikTok shop in Indonesia - Ong, Jesica; Anandya, Dudi; Indarini (Faculty of Business and Economics, University of Surabaya, 2024)
This study aims to examine the factors influencing purchase intention among TikTok Shop consumers in Indonesia. Using a survey of 165 TikTok Shop users, data were analyzed through confirmatory factor analysis (CFA) and structural equation modeling (SEM) via AMOS 24 software. The findings reveal that economy, reliability, interaction, and sales promotion significantly impact consumer purchase intention, while necessity does not. Reliability emerged as the most influential factor, suggesting that consumer trust in accurate and dependable product information on TikTok Shop strongly drives purchase intention. Interaction between consumers and sellers also plays a key role, as engagement fosters a positive shopping experience, further enhancing purchase intentions. Additionally, the economy and sales promotion factors, such as discounts and shipping subsidies, positively affect consumer purchase behavior. These results indicate that TikTok Shop could benefit from strengthening its reliability and interactive features to improve consumer experiences and encourage purchases. Future research could investigate regional and demographic variations, especially among older age groups, to deepen insights into consumer behavior across social commerce platforms.